Arbuscular Mycorrhizal Fungal 14-3-3 Proteins Are Involved in Arbuscule Formation and Responses to Abiotic Stresses During AM Symbiosis - Sun, Zhongfeng; Song, Jiabin; Xin, Xi’an; Xie, Xianan; Zhao, Bin (Frontiers in Microbiology, 2018)
Arbuscular mycorrhizal (AM) fungi are soil-borne fungi belonging to the ancient phylum Glomeromycota and are important symbionts of the arbuscular mycorrhiza, enhancing plant nutrient acquisition and resistance to various abiotic stresses. In contrast to their significant physiological implications, the molecular basis involved is poorly understood, largely due to their obligate biotrophism and complicated genetics. Here, we identify and characterize three genes termed Fm201, Ri14-3-3 and RiBMH2 that encode 14-3-3-like proteins in the AM fungi Funneliformis mosseae and Rhizophagus irregularis, respectively. The transcriptional levels of Fm201, Ri14-3-3 and RiBMH2 are strongly induced in the pre-symbiotic and symbiotic phases, including germinating spores, intraradical hyphae- and arbuscules-enriched roots. To functionally characterize the Fm201, Ri14-3-3 and RiBMH2 genes, we took advantage of a yeast heterologous system owing to the lack of AM fungal transformation systems. Our data suggest that all three genes can restore the lethal S. cerevisiae bmh1 bmh2 double mutant on galactose-containing media. Importantly, yeast one-hybrid analysis suggests that the transcription factor RiMsn2 is able to recognize the STRE (CCCCT/AGGGG) element present in the promoter region of Fm201 gene. More importantly, Host-Induced Gene Silencing of both Ri14-3-3 and RiBMH2 in R. irregularis impairs the arbuscule formation in AM symbiosis and inhibits the expression of symbiotic PT4 and MST2 genes from plant and fungal partners, respectively. We further subjected the AM fungus-Medicago truncatula association system to drought or salinity stress. Accordingly, the expression profiles in both mycorrhizal roots and extraradical hyphae reveal that these three 14-3-3-like genes are involved in response to drought or salinity stress. Collectively, our results provide new insights into molecular functions of the AM fungal 14-3-3 proteins in abiotic stress responses and arbuscule formation during AM symbiosis.